STUDY ON USE OF FUNDS RURAL PRIORITY FOR RURAL DEVELOPMENT IN ORDER TO ACHIEVE VILLAGE AUTONOMY - Sri Kusriyah (International Journal of Law Reconstruction, 2018)
The government policy in terms of rural development are set to determine the priority of the village budget is used for rural development initially was referring to Act No. 6 of 2014 on the village, Article 1 point 8 states that Rural Development is an effort to improve the quality of life and life to sebesar- the welfare of the village community. Priority use of the Village Fund to finance the implementation of priority programs and activities that cut across the field. among other areas of activity featured products village or rural areas